Nursing of a patient undergoing bilateral knee replacement surgery (1例双膝关节置换术患者的护理体会) - WANG Qiujie (王秋洁); LI Jie (李杰); QIN Jingwen (秦婧文); WANG Xiaojuan (王晓娟); CAI Linlin (蔡琳琳) (中西医结合护理)
This paper summarized the nursing management for a patient undergoing bilateral knee replacement surgery. The psychological care and postoperative preparation were carried out after nursing evaluation. Individualized rehabilitation plan including prevention of postoperative complications, rehabilitation exercise and regular follow-up was implemented to improve the recovery of the patient. (本文总结了1例双膝关节置换术(TKA)患者的护理经验, 入院后针对评估结果开展心理护理, 做好术前准备; 术后实施个体化的快速康复方案, 预防并发症, 早期指导康复训练, 定期随访, 促进患者早日康复。)